Approximation of functions from Weyl-Nagy classes by Zygmund averages - Kostich, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
For functions from the Weyl-Nagy classes, in the uniform metric, we calculate exact-order estimates of the deviations of the Zygmund sums.